Present role and future perspectives of interventional radiology in the treatment of painful bone lesions. (25th April 2018) - Barile, Antonio; Arrigoni, Francesco; Bruno, Federico; Palumbo, Pierpaolo; Floridi, Chiara; Cazzato, Roberto L; Reginelli, Alfonso; Zappia, Marcello; Brunese, Luca; Zugaro, Luigi; Masciocchi, Carlo
Interventional radiology has experienced an exponential growth in the last years. Nowadays it is possible to treat painful benign lesions or metastases with optimal results in terms of pain management and disease control. Among the benign lesions, osteoid osteoma is the most frequently treated with minimal invasive techniques and the results are excellent. Another lesion, traditionally treated with surgery (osteoblastoma) represent today another field of application. In the oncological field, metastases are, numerically, the most diffuse indications for treatment. Research carried out during the last decades has provided the interventional radiologist with a great variety of techniques of ablation and devices for monitoring the sensitive structures close to the target lesion. New ablation techniques and monitoring devices contribute to the achievement of significantly increasing rates of effectiveness and safety of interventional radiology procedures.